The Effect of Flipped Learning Method on Students' Speaking of Auditory and Visual Learning Styles at vocational high school - Yazid, Puan Azchira; Suprayetno, Edi; Rahmadhani, Maitri (Institut Agama Islam Negeri Palopo, 2024)
This study aimed to analyze and determine the effect of using the Flipped Learning Method on the speaking skills of students with visual and auditory learning styles at SMK Al Maksum Stabat, as well as to examine the differing impacts on these two groups. A quasi-experimental research design was employed, involving 58 students selected from a total population of 446 through purposive sampling. The participants were divided into two classes: X BDP with 23 students as the experimental group and X MP1 with 35 students as the control group. The study's findings indicated that the Flipped Learning Method significantly improved the speaking skills of both groups. Visual learners showed a mean score increase of 9.64 points (p-value 0.000 < 0.05), while auditory learners exhibited a mean score increase of 7.22 points (p-value 0.000 < 0.05), both indicating statistically significant improvements. Furthermore, the comparison of mean differences suggested a slightly greater impact on the speaking skills of visual learners. Correlation analysis supported these results, with strong positive correlations between pre-test and post-test scores for visual learners (r = 0.822) and auditory learners (r = 0.925), confirming the different effectiveness of the Flipped Learning Method, with a marginally higher benefit observed for visual learners.